1987
DOI: 10.1029/jb092ib12p12869
|View full text |Cite
|
Sign up to set email alerts
|

Impact craters of Venus: A continuation of the analysis of data from the Venera 15 and 16 spacecraft

Abstract: Additional studies of Venusian impact craters have been made based on an analysis of Venera 15/16 radar imagery and altimetry. The crater population on Venus has been subdivided into groups representing different morphological classes and types. The craters display the size‐dependent variations in morphology which are well known from other planets. Assuming a crater production rate based on estimates by Hartmann et al. (1981), their areal density indicates an age for the total population of approximately 1 b.y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 12 publications
3
66
1
Order By: Relevance
“…This is well known (Ivanov et al 1986, Basilevsky et al 1987, Phillips et al 1991, Zahnle 1992, Herrick and Phillips 1994, McKinnon et al 1997. But precisely how large an asteroid must be to crater the surface, or by how much a somewhat larger asteroid is slowed, or how large the consequent crater will be, are not quantities known with any great confidence.…”
Section: Introductionmentioning
confidence: 85%
“…This is well known (Ivanov et al 1986, Basilevsky et al 1987, Phillips et al 1991, Zahnle 1992, Herrick and Phillips 1994, McKinnon et al 1997. But precisely how large an asteroid must be to crater the surface, or by how much a somewhat larger asteroid is slowed, or how large the consequent crater will be, are not quantities known with any great confidence.…”
Section: Introductionmentioning
confidence: 85%
“…A number of groups have studied the disruption and destruction of bolides striking deep atmospheres (e.g., Passey and Melosh 1980, Basilevsky et al 1987, Ivanov 1988, Ivanov et al 1992, Zahnle 1992, Chyba et al 1993, Chevalier and Sarazin 1994, Boslough et al 1994, Ahrens et al 1994, Takata et al 1994, Field and Ferrara 1995, Svetsov et al 1995, Svetsov 1996, Mac Low 1996, Zahnle 1996, Crawford 1996, 1997, Roulston and Ahrens 1997. The consensus seems to be that impacting bodies of a certain size are disrupted by aerodynamic forces and that mechanical ablation (as opposed to radiative ablation, which is the usual fate of small meteors) plays a major role in the deceleration of the object as a whole (Field and Ferrara 1995, Svetsov et al 1995, Mac Low 1996, Crawford 1996.…”
Section: Overall Frameworkmentioning
confidence: 97%
“…If this is indeed the case, we would predict the highest crater density in the polar regions and a general decrease in crater density from the polar regions toward the equatorial highlands. Using the data of Basilevsky et al (1987) showing the locations of identified impact craters, Head et al (1988) plotted absolute crater density as a function of latitude in equal area latitude bands ( Figure 5). The resulting plot shows a distinctive and statistically significant trend from higher crater density in the polar region to lower crater density at 30" North latitude, where the VENERA 15/16 data coverage terminates, On the basis of this analysis, we conclude that there is evidence for a trend of decreasing age from the north polar region toward the equator.…”
Section: Youngingtrendfrompoletoequatormentioning
confidence: 99%
“…5. The number of craters in equal area bands (10' km*) from the north pole to about 30" north latitude on Venus, based on the data of Basilevsky et al (1987). Greater latitude width of lowermost latitude band is due to the slightly uneven latitude coverage of the VENERA 15/16 data in this area.…”
Section: Youngingtrendfrompoletoequatormentioning
confidence: 99%